Midterm Outcome of Transumbilically Laparoscopic-Assisted Versus Laparoscopic and Open Appendectomy in Children—A Matched Prospective Study - Bergholz, Robert; Klein, Ines; Wenke, Katharina; Boettcher, Michael; Reinshagen, Konrad; Krebs, Thomas (European Journal of Pediatric Surgery, 2015)
Background Prospective data of transumbilically laparoscopic-assisted appendectomies (TULAA) is absent in the pediatric population. We therefore compared the midterm outcome of TULAA with open (OA) and laparoscopic (LA) appendectomies in children with appendicitis in a matched prospective study.Methods A total of 20 patients operated with TULAA were matched to 20 cases operated by LA and OA, respectively, according to sex, age, and histology of the resected appendix. All 60 children were evaluated during a 3-month follow-up visit.Results The subjective pain level after discharge, the rate of complications, and persistent painful wound as well as the duration of days refraining from school or kindergarten were similar in all three groups. The wound satisfaction was significantly higher in TULAA and LA. Children operated with TULAA had a faster return to full physical activity compared with OA.Conclusion Our data suggest that TULAA, LA, and OA have a similar outcome 3 months after surgery apart from cosmetic appearance of the wound and return to full physical activity in pediatric patients. Whether parental bias or the increased wound satisfaction act as confounders for early return to full physical activity should be evaluated in larger prospective randomized trials.
Keywords: TULAA; laparoscopic; appendectomy; SILS; appendicitis